Reducing rotors clearance - a way to increase the performance of a screw compressor. Issue 1 (September 2021) - Nitulescu, M; Slujitoru, C; Petrescu, V; Silivestru, V; Fetea, G; Tomescu, S
Abstract: The screw compressors due to their constructive simplicity and the known advantages in operation is increasingly demanded on the market. Many companies are producing this type of compressor. The influence of leakages – conditioned by rotors clearances – on compressor performance is well known. The literature addresses the problem of coatings, but for dry compressors. Our intention is to apply this technology in the case of oil injected screw compressors (when the profile deviation is large or in the case of rotors with slight wear). Tests were performed to evaluate the performance of a screw compressor with uncoated rotors and performance of compressor assembled with coated rotors (both pairs of rotors have the same profile deviations – the profile accuracy measured is -8 ÷ -10 μm). The test aim to highlight only the influence of the coating layer – by reducing clearances – on the performance of the compressor, without performing further quality test of the coated layer. The quality of the coating process is the subject of additional research. We intend to use this technology for oil injected screw compressors both for new manufactured rotors (with large profile tolerances) and rotors with slight.